MENDUDUKAN ULANG PERAN DAN WEWENANG PENANGANAN PELANGGARAN TINDAK PIDANA PEMILU OLEH BADAN PENGAWAS PEMILIHAN UMUM - Jamaludin, Ahmad (Jurnal Keadilan Pemilu, 2023)
The Election Supervisory Body Regulation No. 7 of 2022 and the Republic of Indonesia Election Supervisory Body Regulation No. 3 of 2023 concerning the Integrated Law Enforcement Center for Elections underline the role of Bawaslu in handling election violations, including criminal election acts, which are serious legal infringements in the context of elections. Bawaslu acts in a law enforcement capacity, tasked with investigating alleged election violations. This includes verifying the fulfillment of formal and material requirements of the reports and identifying types of suspected violations, akin to the investigative function in the Criminal Code, which should be conducted by officers of the Indonesian National Police. This study aims to explore the conception of handling criminal election violations by Bawaslu, particularly in its involvement in the Gakkumdu structure. The methodology employed in this research is juridical-normative. As a finding, this study concludes that the history of Indonesian democracy records a significant shift in the role of Bawaslu, occurring in line with the changing political dynamics and societal demands for transparency and accountability in elections. With the basis of Law No. 7/2017, Bawaslu also functions in the enforcement of election law, analogous to judicial institutions. Despite contradictions with the principle of separation of powers, the ‘new separation of powers’ approach categorizes it as an independent body. Bawaslu plays a critical role in overseeing administrative election violations, including monitoring, prevention, and enforcement actions. As part of Gakkumdu alongside the police and the prosecutor's office, Bawaslu coordinates in the enforcement of criminal election law, yet it should only act as a reporting entity, not as a direct handler of criminal election cases. The effectiveness of Gakkumdu is sometimes impeded by differing legal perceptions, necessitating an evaluation of its processes and work structure.